MODALITAS POLITIK PEMENANGAN BUPATI PEREMPUAN PERTAMA DI KABUPATEN KARANGASEM (STUDI KASUS: KEMENANGAN GUSTI AYU MAS SUMATRI DALAM PILKADA KARANGASEM TAHUN 2015) (Jurnal Nawala Politika, 2023)
Women's rights in the dynamics of political power in Bali tend to be placed in a space that is not exponential. In the constellation of regional elections in Bali, the election of women as regional heads is only filled in 2 out of 9 regencies, where one of the women's election occurred in Karangasem Regency. In the 2015 Karangasem regional head election (Pilkada), I Gusti Ayu Mas Sumatri in the candidate pair